2012
DOI: 10.1038/nsmb.2457
|View full text |Cite
|
Sign up to set email alerts
|

The ATPase domain of ISWI is an autonomous nucleosome remodeling machine

Abstract: ISWI slides nucleosomes along DNA, enabling the structural changes of chromatin required for the regulated use of eukaryotic genomes. Prominent mechanistic models imply cooperation of the ISWI ATPase domain with a C-terminal DNA-binding function residing in the HAND-SANT-SLIDE (HSS) domain. Contrary to these models, we show by quantitative biochemical means that all fundamental aspects of nucleosome remodeling are contained within the compact ATPase module of Drosophila ISWI. This domain can independently asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
129
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(143 citation statements)
references
References 58 publications
13
129
1
Order By: Relevance
“…Our observation of the open form of Mot1 in 6Fe DNA complexes is consistent with the open form of the ATPase in the SsoRad54-DNA co-complex (28). In contrast, in solution, interconversion between conformational forms of Swi/Snf ATPases has been observed (31,58), and the closed form predominated when bound to DNA in solution (31), consistent with results using the Moyle6Fe template. We favor a model in which the Mot1 open and closed forms both exist in solution in the absence of ATP.…”
Section: Dna Sequence Effects On Mot1supporting
confidence: 79%
“…Our observation of the open form of Mot1 in 6Fe DNA complexes is consistent with the open form of the ATPase in the SsoRad54-DNA co-complex (28). In contrast, in solution, interconversion between conformational forms of Swi/Snf ATPases has been observed (31,58), and the closed form predominated when bound to DNA in solution (31), consistent with results using the Moyle6Fe template. We favor a model in which the Mot1 open and closed forms both exist in solution in the absence of ATP.…”
Section: Dna Sequence Effects On Mot1supporting
confidence: 79%
“…In this work the authors found that ISWI lacking its HSS domain can still remodel nucleosomes, with an intrinsic ability to bind nucleosomes and to interact with histone H4 N terminus, revealing a positive role for the HSS domain in increasing the affinity and specificity of ISWI ATPase for nucleosome ( Fig. 2) (Mueller-Planitz et al 2013). Similarly, another study showed a regulatory function for the SLIDE domain of Saccharomyces cerevisiae Isw2 subunit to help maintaining the directionality of DNA movement into nucleosomes (Hota et al 2013).…”
Section: Regulation Through Structural and Functional Iswi Domainsmentioning
confidence: 87%
“…Over the past few years, in vivo and in vitro studies have led to a broadly accepted model in which the HSS domain plays an integral part during the remodelling reaction (Boyer et al 2004;Grune et al 2003a;Boyer et al 2002). Unexpectedly, a recent study conducted on Drosophila ISWI (d ISWI) showed that most of the fundamental regulatory aspects of nucleosome remodelling are contained around the compact ATPase module (Mueller-Planitz et al 2013). In this work the authors found that ISWI lacking its HSS domain can still remodel nucleosomes, with an intrinsic ability to bind nucleosomes and to interact with histone H4 N terminus, revealing a positive role for the HSS domain in increasing the affinity and specificity of ISWI ATPase for nucleosome ( Fig.…”
Section: Regulation Through Structural and Functional Iswi Domainsmentioning
confidence: 99%
See 2 more Smart Citations